Oasis [compact disc] - Balvin, J; Bad Bunny, 1994- (Universal Music Latino, 2019)
J. Balvin and Bad Bunny have seen their popularity skyrocket beyond the Latin music charts. Now, these two superstars have joined forces on a new album that includes the single Que Pretendes.